Co-Occurrence of Posttraumatic Stress Disorder and Cardiovascular Disease Among Ethnic/Racial Groups in the United States. Issue 7 (September 2018) - Vidal, Carmen; Polo, Ruth; Alvarez, Kiara; Falgas-Bague, Irene; Wang, Ye; Lê Cook, Benjamin; Alegría, Margarita
ABSTRACT: Objective: Trauma and/or symptoms of posttraumatic stress disorder (PTSD) have been linked to the onset of cardiovascular disease (CVD), but the exact mechanism has not been determined. We examine whether the risk of CVD is different among those who have a history of trauma without PTSD symptoms, those who have experienced trauma and developed any symptoms of PTSD, and those with a PTSD diagnosis. Furthermore, we examine whether this association varies across ethnic/racial groups. Methods: We used two data sets that form part of the Collaborative Psychiatric Epidemiology Surveys - the National Latino and Asian American Study and the National Comorbidity Survey Replication. Results: We found an increased likelihood of cardiovascular events for those with a diagnosis of PTSD (odds ratio [OR] = 2.10, 95% CI = 1.32–3.33) when compared with those who had not experienced trauma. We did not find an increased risk for those who had experienced trauma without symptoms or with subclinical symptoms of PTSD. The higher likelihood of having a cardiovascular event in those with PTSD was significant for non-Latino whites (OR = 1.86, 95% CI = 1.08–3.11), Latinos (OR = 1.94, 95% CI = 1.04–3.62), and non-Latino blacks (OR = 3.73, 95% CI = 1.76–7.91), but not for Asian respondents. Conclusions: The constellation of symptoms defining PTSD diagnosis reflect adverse reactions to traumatic events and indicate that complex responses to traumatic events may be a risk factor for CVD. Abstract : Supplemental digital content is available in the text.